Mercy as a Factor of Social Cohesion: Evacuation to Uzbekistan During the Great Patriotic War (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article is devoted to the spiritual feat of the Uzbek people during the Great Patriotic War. The processes of receiving the evacuated population from the western territories of the Soviet Union occupied by the Nazis, providing them with housing, clothing, food, work and education, individual and collective reception of children, as well as difficulties that arose in the activities of the republic's orphanages, were analyzed.